Proto-Slavic origins of Hutsul song-chronicles (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article suggests revisiting the problem of dating of the Hutsul folklore genre known as spivanky-khroniky, i.e. songs about events. The article claims that they could be rather regarded as an independent development, parallel to the Ukrainian dumas, bylynas, South Slavic epics, nevertheless based on the common-Slavic folklore heritage.
Keywords: the Ukrainian language; language of folklore; Indo-European poetics; Common-Slavic poetics